Habilidades de Mindfulness y Cognición Social en la predicción de la sintomatología afectiva en Esquizofrenia, Trastorno Obsesivo-Compulsivo y controles sanos - González-Panzano, Manuel; Borao, Luis; Herrera-Mercadal, Paola; Campos, Daniel; López-del-Hoyo, Yolanda; Morillo, Héctor; García-Campayo, Javier (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract: Mindfulness and social cognition skills in the prediction of affective symptomatology in schizophrenia, obsessive-compulsive disorder and nonclinical participants. The aim of the study was to investigate significant predictors of affective symptomatology in schizophrenia, obsessive-compulsive disorder and healthy controls. The sample was of 91 participants who completed the following instruments: the Eye Test (emotional recognition), the Hinting Task (theory of mind), the Ambiguous Intentions and Hostility Questionnaire(AIHQ; attributional style), Interpersonal Reactivity Index (IRI; empathy), the Mindful Attention Awareness Scale (MAAS; mindfulness trait), the Five Facet Mindfulness Questionnaire-Short Form(FFMQ-SF), and the Hospital Anxiety and Depression Scale(HADS). Significant predictors of affective symptomatology were: mindfulness (dispositional or trait mindfulness, nonreactivity and nonjudgment), and social cognition (SC) (attributional style and theory of mind). Mediation analysis showed that theory of mind was the only significant mediator of affective symptomatology. This paper shows the role of mindfulness and SC skills in the prediction of affective symptomatology. Keywords: mindfulness, social cognition, theory of mind, affective symptomatology, schizophrenia, obsessive-compulsive disorder. Resumen:El objetivo del estudio fue investigar predictores significativos de sintomatología afectiva en Esquizofrenia (EZ), trastorno obsesivo compulsivo (TOC) y controles no clínicos. La muestra fue de 91 participantes que completaron los siguientes instrumentos: Eyes Test (reconocimiento emocional), Hinting Task (teoría de la mente), Ambiguous Intentions and Hostility Questionnaire (AIHQ; estilo atribucional), Índice de Reactividad Interpersonal (IRI; empatía), Mindful Attention Awareness Scale (MAAS;mindfulness rasgo), Five Facet Mindfulness Questionnaire-Short Form (FFMQ-SF), y Hospital Anxiety and Depression Scale (HADS).Los resultados mostraron que el mindfulness (mindfulness rasgo, no reactividad y no juicio) y la cognición social (estilo atribucional y teoría de la mente) fueron predictores significativos. Los análisis de mediación señalaron la variable de teoría de la mente, como único mediador significativo de la sintomatología afectiva.Los resultados de este estudio señalan el papel de las habilidades de mindfulness y cognición social en la predicción de sintomatología afectiva. Palabras clave: mindfulness, cognición social, teoría de la mente, sintomatología afectiva, esquizofrenia, trastorno obsesivo-compulsivo.